2007
DOI: 10.1016/j.npep.2006.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Intra-VTA CART 55-102 reduces the locomotor effect of systemic cocaine in rats: An isobolographic analysis

Abstract: CART (cocaine-and amphetamine-regulated transcript) peptides appear to be mediators or modulators of psychostimulant drugs. An interesting result in the nucleus accumbens has been that injection of CART peptide has no effect by itself on locomotor activity, but it reduces the locomotor activity induced by cocaine or amphetamine. However, in the ventral tegmental area (VTA), injections of CART peptide have been shown to increase locomotor activity, although to a lesser degree (Kimmel et al. 2000). This study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Scale bar ¼ 200 mm. (Vaarmann and Kask, 2001;Choi et al, 2003;Yang et al, 2004;Hunter et al, 2006;Jaworski et al, 2007;Ma et al, 2007), and it is possible that antidepressant action of CART may be mediated via some of these neurotransmitters.…”
Section: Effect Of Icv and Intra-cea Administration Of Cart On Depresmentioning
confidence: 99%
See 1 more Smart Citation
“…Scale bar ¼ 200 mm. (Vaarmann and Kask, 2001;Choi et al, 2003;Yang et al, 2004;Hunter et al, 2006;Jaworski et al, 2007;Ma et al, 2007), and it is possible that antidepressant action of CART may be mediated via some of these neurotransmitters.…”
Section: Effect Of Icv and Intra-cea Administration Of Cart On Depresmentioning
confidence: 99%
“…CART may modulate affective and anxiety behaviors (Stanek, 2006) and exert an augmenting effect in the treatment of depression because it acts as a putative and potential neurotransmitter/cotransmitter that is also involved in psychostimulant action (Jaworski et al, 2003;Jones and Kuhar, 2006). Preliminary results suggest that, CART directly controls the expression of several important neurotransmitters, which are instrumental in processing neuropsychological behaviors (Vaarmann and Kask, 2001;Yang et al, 2004;Jaworski et al, 2007). Ma et al (2007) have suggested that an increase in 5-hydroxytryptamine (5-HT) may contribute to the antidepressant-like effect of CART.…”
Section: Introductionmentioning
confidence: 99%
“…Weak psychostimulant-related effects are seen after injections of CART peptide into the VTA [ 17,22 ]. Intra-NAcc injections of CART alone have no effect on locomotion, but inhibit locomotion produced by systemic injections of amphetamine [ 21 ] and cocaine [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the VTA in particular, the CART peptide seems to act as a potent stimulator of locomotor activity and conditioned place preference (Jaworski et al , 2003(Jaworski et al , , 2007, a form of Pavlovian conditioning also elicited by addictive drugs (Tzschentke , 1998 ). It is thought that the behavioral effects of CART activity in the VTA occur by CART directly stimulating dopaminergic neurons or indirectly un-inhibiting gamma-amino-butyric-acid-ergic interneurons .…”
Section: Discussionmentioning
confidence: 99%